Edward Blyth, John M'Clelland, the curatorship of the Asiatic Society's collections and the origins of the Calcutta journal of natural history. Issue 2 (October 2015) - Mathew, J.
Abstract : This paper explores the origins of the Calcutta journal of natural history (1841–1848) and the search from the 1830s for a permanent curator for the collections of the Asiatic Society of Bengal. Edward Blyth (1810–1873) was appointed, even though John M'Clelland (or McClelland) (1805–1883), who founded the Calcutta journal of natural history, had acted as part-time curator of the collections for two years before Blyth's arrival in Calcutta. An analysis of the Society and the journal allows reconsideration of the significance of natural history in India in the mid-nineteenth century.